Letters to the chairman of the committee of the honourable the House of Commons on the agricultural distresses, stating the causes of those distresses and pointing out the remedies for them . and to David Ricardo, ... in answer to his speech of the 7th of March, 1821 ... /; (printed for J.M. Richardson [etc.], 1821)
In: Dissertation on lime ... / by Thomas Hornby.